Evaluación de cuatro distanciamientos de siembra en el desarrollo y producción de dos variedades del Brócoli (brassicaoleracea l.) en el cantón Ibarra provincia de Imbabura - Montalvo Muñoz, Favio Leandro (2014)
This research was conducted in the Canton Ibarra, Imbabura province, in order to study four planting distances in the development and production of two varieties of broccoli (Brassica oleracea L.), established treatments are two varieties of broccoli and Legacy Avenger at planting distances of 0.30 x 0.60; 0.40 x 0.60 and 0.50 x 0.60 m and 0.35 x 0.60 witness with m related to commercial planting in the area. To research the split plot design (DPV) with 2 treatments and four subtratamientos and a control for each treatment in three replications was used. The experimental plots correspond to an area of 16.0 m² and total area of 384 m² experiment, the variables were evaluated: plant height at 20, 40 and 60 (dat), days to flowering, days to harvest, pellet size, pellet weight at time of harvest and yield in kg/ha. All variables are subjected to analysis of variance, using the Tukey test at 5%. The results found that the treatments with (broccoli varieties) based on planting distances are appropriate for applied research